Apatinib weakens resistance of gastric cancer cells to paclitaxel by suppressing JAK/STAT3 signaling pathway. Issue 2 (18th August 2021) - Bei, Yanping; Chen, Xue; Xu, Quan; Lv, Jiaming; Hu, Jing; Yang, Shaohui
Abstract: Apatinib has experienced a long‐term study in enhancing the sensitivity of various cancer cells to chemotherapy drugs. Currently, researches show that apatinib could attenuate the resistance of gastric cancer (GC) cells to paclitaxel (PTX), but the mechanism has not been fully elucidated, which therefore was explored in this study. PTX‐resistant GC cell, namely HGC‐27R, was established by exposure to stepwise‐increasing PTX. The cell viability of HGC‐27 and HGC‐27R under PTX or apatinib at different concentrations was assessed by CCK‐8 assay, while scratching test and invasion assay were used for investigating the harmful influence of GC cells resistance to PTX. The function of apatinib in HGC‐27R was studied by performing functional experiments (flow cytometry, scratching test, and invasion assay). Western blot was performed to measure the expressions of proteins concerning apoptosis, epithelial‐mesenchymal transition and janus‐activated kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. PTX‐resistant GC cell, namely HGC‐27R, was successively constructed. HGC‐27R cells showed resistance to PTX by promoting migratory and invasive capabilities. Apatinib not only inhibited cell viability of HGC‐27 and HGC‐27R, but also combined with PTX to suppress that of HGC‐27R. Apatinib enhanced apoptosis, diminished migration and invasion of HGC‐27R cells, elevated proapoptotic protein expression, and reduced Bcl‐2, vimentin, snail, MMP‐3, MMP‐2, and MMP‐9 expressions. The phosphorylation of JAK2 and STAT3 was repressed by apatinib. JAK2 partially reversed the effect of apatinib on enhancing sensitivity of GC cells to PTX. Apatinib strengthened sensitivity of GC cells to PTX by inhibiting JAK/STAT3 signaling pathway.